2020
DOI: 10.17138/tgft(8)133-140
|View full text |Cite
|
Sign up to set email alerts
|

Selection based on meiotic behavior in <i>Urochloa decumbens</i> hybrids from non-shattered seed

Abstract: This study aimed to evaluate the end-products of meiosis in sexual and apomictic hybrids of Urochloa decumbens, so as to identify genotypes with good production of viable pollen for use in breeding programs to increase yields of pure viable seed and reduce degree of seed shattering. From 457 intraspecific hybrids of U. decumbens arising from crosses between 3 artificially tetraploidized sexual plants and the apomictic cultivar Basilisk, 27 hybrids from non-shattered seed were selected. Slides were prepared by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 2 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…Lutts et al (1991) studied the relationship between uni-, bi-, and multivalent in metaphase I with pollen viability and seed yield and concluded that chromosome associations cannot be used to evaluate the fertility level of F 1 hybrids from the crossing of U. ruziziensis × U. decumbens and U. ruziziensis × U. brizantha. Meanwhile, most studies report that a low frequency of meiotic abnormalities is associated with viable pollen production and consequent fertility in Urochloa, while the high frequency of irregularities is associated with inviable pollen featuring low production of fertile seeds (Adamowski et al 2008, Souza et al 2015, Paula et al 2016, Rocha et al 2019, Baldissera et al 2020. Souza et al (2015) reported that some hybrids of U. decumbens showed a peculiar behavior because 100% of the tetrads were affected, although pollen sterility was lower than expected.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lutts et al (1991) studied the relationship between uni-, bi-, and multivalent in metaphase I with pollen viability and seed yield and concluded that chromosome associations cannot be used to evaluate the fertility level of F 1 hybrids from the crossing of U. ruziziensis × U. decumbens and U. ruziziensis × U. brizantha. Meanwhile, most studies report that a low frequency of meiotic abnormalities is associated with viable pollen production and consequent fertility in Urochloa, while the high frequency of irregularities is associated with inviable pollen featuring low production of fertile seeds (Adamowski et al 2008, Souza et al 2015, Paula et al 2016, Rocha et al 2019, Baldissera et al 2020. Souza et al (2015) reported that some hybrids of U. decumbens showed a peculiar behavior because 100% of the tetrads were affected, although pollen sterility was lower than expected.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of one or two micronuclei in a tetrad would result in a ratio of 3:1 and 2:2 for viable and inviable pollen grains, respectively. According to Baldissera et al (2020), tetrads that presented micronucleus in three or four microspores were more detrimental to the production of viable pollen than those with micronuclei in only one or two microspores. However, the lack of association between the variables Mcn1 and Mcn2 with the seed set does not reinforce this hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations